Lycopene Prevents Mitochondrial Dysfunction during d‑Galactosamine/Lipopolysaccharide-Induced Fulminant Hepatic Failure in Albino Rats - Sheriff, Sheik Abdulazeez; Shaik Ibrahim, Shaikhussain; Devaki, Thiruvengadam; Chakraborty, Sandipan; Agarwal, Subhash; Pérez-Sánchez, Horacio (Journal of proteome research, 2017)
Functional perturbation of mitochondria is associated with fulminant hepatic failure (FHF). d-Galactosamine/lipopolysaccharide (d-GalN/LPS)-induced FHF is a renowned model to evaluate the efficacy of hepatoprotective agents. Lycopene is an antioxidant and phytonutrient from the carotenoid family. The health benefits of lycopene are prominent against cancer and cardiovascular, lung, liver, and skin problems. Recent studies have demonstrated the hepatoprotective, antidyslipidemic, and antioxidant roles of lycopene. The current study was designed to appraise the ability of lycopene to prevent mitochondrial dysfunction during the d-GalN/LPS-induced FHF. The administration of d-GalN/LPS (300 mg and 30 μg/kg body weight, respectively) to the experimental rats induced several disturbances in mitochondrial function. The lipid peroxide and hydrogen peroxide levels were increased (p < 0.05). The activities of mitochondrial antioxidants, tricarboxylic acid (TCA) cycle, and electron transport chain enzymes and the cellular adenosine triphosphate (ATP) content were decreased (p < 0.05). Lycopene (10 mg/kg body weight for 6 days) pretreatment attenuated lipid peroxidation and prohibited the excessive synthesis of hydrogen peroxide. The d-GalN/LPS-induced impairment in ATP production and increased enzyme activities were effectively prevented by the lycopene administration. The lycopene-mediated mitochondrial protection was mainly ascribed to the strong antioxidant potential of this phytonutrient. Molecular modeling results obtained show evidence that lycopene inhibits several lipoxygenases and provides rationale for the observed prevention of lipid peroxidation in the mitochondrial membrane. The carotenoid lycopene combatted oxidative stress, scavenged free radicals, prevented ROS generation, and inhibited the toxic effects of d-GalN/LPS during FHF.